Promoting Youth’s Self-Empowerment in Residential Care — the Influence of the Organisation: The first year of the project “Creating Futures” and its Swiss–Hungarian Community of Practice - Schmid, Anna (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
In the project “Creating Futures”, youths, staff, and leaders from youth homes in Switzerland and Hungary collaborate in a Community of Practice. Their goal is to develop organisational innovations that allow each of the youth homes to more effectively promote the self-empowerment of young people: their ability to take charge of their own lives and realise their own ideas of the future. This paper reports results, learnings, and first impacts regarding both the topic and the collaborative process in the project’s first formalised year, 2019. In developing its ways of working, the Community of Practice aims to engage as many persons as possible in each youth home. Through focus group discussions, a literature review, and a Young Expert Exchange, organisational factors that promote self-empowerment in residential care have been identified. Representatives of each youth home have selected those of most interest and have begun to assess their existing good practice as well as needs and potentials for innovation. The article includes the voices of participants as it reflects on the requirements for, and benefits and challenges of, youth participation and collaboration within a highly diverse Community of Practice.